THE PERCEPTIONS ON THE USE OF INSTAGRAM FOR VOCABULARY MASTERY - Amelia Indarni; Syofia Delfi; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aims to analyze students’ perceptions on Instagram forvocabulary mastery. This research used quantitative research to descriptiveapproaches. The instrument utilized in this study will be a questionnaire. Thisstudy’s population included 117 students from three classes, with 38 serving as asample. The data was collected in the classroom by sharing the questionnaire aboutusing Instagram for vocabulary improvement. Microsoft word and Microsoft excel2019 were utilized to analyze the questionnaire data of the students, as well as togain the validity, reliability and normality of the instrument the writer used SPSS 25.The data demonstrated that overall score of students’ questionnaire result from 38students with the average score 99,2 (66,1%) out of 150 (100%) which means morethan half items are agreed by participants that Instagram has role in students’vocabulary mastery. Based on the findings, therefore recommended for others thatthe first-year students of English Department can gain information more aboutvocabulary through Instagram and also the teacher may guide the students toimprove students’ ability in vocabulary mastery by doing activities in the classroom.Keywords: Perceptions; Instagram; Vocabulary mastery